2021
DOI: 10.1038/s41385-021-00439-x
|View full text |Cite
|
Sign up to set email alerts
|

An integrin αEβ7-dependent mechanism of IgA transcytosis requires direct plasma cell contact with intestinal epithelium

Abstract: Efficient IgA transcytosis is critical for the maintenance of a homeostatic microbiota. In the canonical model, locally-secreted dimeric (d)IgA reaches the polymeric immunoglobulin receptor (pIgR) on intestinal epithelium via simple diffusion. A role for integrin αE(CD103)β7 during transcytosis has not been described, nor its expression by intestinal B cell lineage cells. We found that αE-deficient (αE−/−) mice have a luminal IgA deficit, despite normal antibody-secreting cells (ASC) recruitment, local IgA pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Itgβ7 can pair with Itgα4 and ItgαE chains to form the heterodimeric Itgα4β7 and ItgαEβ7 surface receptors. Itgα4β7 is crucial for the recruitment of immune cells to the LP, whereas ItgαEβ7 is expressed on a subset of IgA + PC and establishes the contact with intestinal epithelial cells, thereby promoting transcytosis of IgA 55 , 56 . Thus, KLF2 controls Itgβ7-mediated recruitment of IgA + PC to the LP and might be involved in ItgαEβ7-mediated interaction of IgA + PC with the epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Itgβ7 can pair with Itgα4 and ItgαE chains to form the heterodimeric Itgα4β7 and ItgαEβ7 surface receptors. Itgα4β7 is crucial for the recruitment of immune cells to the LP, whereas ItgαEβ7 is expressed on a subset of IgA + PC and establishes the contact with intestinal epithelial cells, thereby promoting transcytosis of IgA 55 , 56 . Thus, KLF2 controls Itgβ7-mediated recruitment of IgA + PC to the LP and might be involved in ItgαEβ7-mediated interaction of IgA + PC with the epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Guzman and colleagues revealed that a subpopulation of IgA plasmablasts in the LP express integrin αEβ7 allowing them to interact physically with IECs via E-Cadherin ( Figure 2 ). This intimate plasma cell-IEC interaction allows the efficient transcytosis of dimeric IgA via the poly-IgR (p-IgR) on IECs to the gut lumen ( 83 ). Dimeric IgA consist of two IgA monomers that are covalently connected by the joining chain (J-chain) ( 84 , 85 ).…”
Section: Iga Plasma Cell Interaction With the Intestinal Epitheliummentioning
confidence: 99%
“…In another study, the analysis of liver cells from TCDD-treated mice showed that AhR can potentially induce the expression of E-Cadherin when interacting with KLF6 as a co-activator ( 170 ). As E-cadherin may be necessary for cell-cell interaction between IECs and lymphocytes in the intestine ( 83 ), this mechanism has to be considered when analyzing the role of AhR in the intestinal plasma cell niche. However, functional studies are still missing, and it must be determined whether AhR interacts with KLF6 to induce E-Cadherin in IECs.…”
Section: The Impact Of Nutrients On the Intestinal Epithelium And Iga...mentioning
confidence: 99%
See 1 more Smart Citation
“…The AKT signaling pathway ultimately mediates cell survival, thereby inhibiting apoptosis and increasing the production of plasma cells [ 93 , 94 ]. Likewise, toll-like receptor 9 (TLR9) also triggers the interaction of α4β1 integrins with VCAM-1, which promotes the retention and homing of circulating B cells in secondary lymphoid organs, and homing of the post-germinal central memory B cells into bone marrow or mucosal tissues to differentiate into plasma cells [ 95 ]. Research showed that IgA was secreted into the enteric cavity directly by the docking between αEβ7+ plasma cells and E-cadherin-expressing enterocytes, which identified αEβ7 integrins as an important target for the treatment of inflammatory bowel disease and provides new approaches for drug research and development, such as with natalizumab and vedolizumab.…”
Section: Potential Influence Of Integrins On Immune Cellsmentioning
confidence: 99%